2022
DOI: 10.3389/fphar.2022.1027628
|View full text |Cite
|
Sign up to set email alerts
|

Distinct common signatures of gut microbiota associated with damp-heat syndrome in patients with different chronic liver diseases

Abstract: Background: Chronic hepatitis B (CHB) and non-alcoholic fatty liver disease (NAFLD) are prevalent in China. According to traditional Chinese medicine (TCM) theory, damp-heat (DH) syndrome is common in chronic liver disease. However, the biological characteristics related to quantitative diagnosis remain to be determined. This study aimed to identify the consistent alterations in the gut microbiota associated with DH syndrome in patients with CHB or NAFLD.Methods: A total of 405 individuals were recruited, of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…Paraprevotella, Papillibacter, and Butyricimonas were associated with butyrate generation in the intestine, which was favorable to performance of chickens [29][30][31]. Moreover, unclassi ed_c__Clostridia has been implicated in the biosynthesis of SCFA [32]. Our study further demonstrated that Firmicutes, Eisenbergiella, Paraprevotella, unclassi ed_f__Erysipelotrichaceae, and Papillibacter were positively related to butyrate and Bacteroides was negatively related to butyrate.…”
Section: Discussionsupporting
confidence: 62%
“…Paraprevotella, Papillibacter, and Butyricimonas were associated with butyrate generation in the intestine, which was favorable to performance of chickens [29][30][31]. Moreover, unclassi ed_c__Clostridia has been implicated in the biosynthesis of SCFA [32]. Our study further demonstrated that Firmicutes, Eisenbergiella, Paraprevotella, unclassi ed_f__Erysipelotrichaceae, and Papillibacter were positively related to butyrate and Bacteroides was negatively related to butyrate.…”
Section: Discussionsupporting
confidence: 62%
“…diagnosed 21 chronic hepatitis B and 42 NAFLD patients with the classic damp-heat (DH) syndrome group and identified 29 chronic hepatitis B and 28 NAFLD patients as the non-DH syndrome group. They found a decreased relative abundance of the Lachnospiraceae NC2004 group in patients with the DH syndrome compared to the non-DH syndrome ( 45 ). Taken together, these studies were in agreement with our MR analysis that this aforementioned genus plays a protective role in NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Paraprevotella , Papillibacter and Butyricimonas were associated with butyrate generation in the intestine, which was favorable to performance of chickens [ 36 38 ]. Moreover, unclassified_c__Clostridia has been implicated in the biosynthesis of SCFA [ 39 ]. Our study further demonstrated that Firmicutes, Eisenbergiella , Paraprevotella , u nclassified_f__Erysipelotrichaceae , and Papillibacter were positively related to butyrate and Bacteroides was negatively related to butyrate.…”
Section: Discussionmentioning
confidence: 99%